1999
DOI: 10.1037/1064-1297.7.4.444
|View full text |Cite
|
Sign up to set email alerts
|

Chewing gum affects smoking topography.

Abstract: In a previous study, Wrigley's chewing gum was shown to reduce cravings to smoke and nicotine withdrawal when smokers were not allowed access to cigarettes. The present study expanded these findings by examining smoking behavior of 20 dependent cigarette smokers who were allowed free access to cigarettes throughout the study session but were encouraged and rewarded not to smoke. Each experimental session consisted of the participant watching a movie, then waiting an additional 30 min. Half of the participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…For example, recent studies have investigated the influence of chewing gum on smoking behavior as well as on nicotine withdrawal and craving (Cohen, Britt, Collins, al'Absi, & McChargue, 2001;Cohen, Britt, Collins, Stott, & Carter, 1999;Cohen, Collins, & Britt, 1997). Overall, studies conducting in our laboratory show that chewing gum helps with withdrawal when cigarette smokers could not smoke.…”
Section: Discussionmentioning
confidence: 67%
“…For example, recent studies have investigated the influence of chewing gum on smoking behavior as well as on nicotine withdrawal and craving (Cohen, Britt, Collins, al'Absi, & McChargue, 2001;Cohen, Britt, Collins, Stott, & Carter, 1999;Cohen, Collins, & Britt, 1997). Overall, studies conducting in our laboratory show that chewing gum helps with withdrawal when cigarette smokers could not smoke.…”
Section: Discussionmentioning
confidence: 67%
“…Recent studies conducted in our laboratory have demonstrated that simple alternatives to smoking, such as chewing gum, may influence urge to smoke and nicotine withdrawal (Cohen, Britt, Collins, Stott, & Carter, 1999;Cohen, Collins, & Britt, 1997). Cohen et al (1997) assessed the effects of temporary deprivation (approximately 3 hours) on nicotine withdrawal and craving symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Others suggested that smokers reported fewer cigarette puffs and the time until they first lit their first cigarette increased significantly. 26 The chewing gum was, also, a factor that helped smokers to deal with withdrawal symptoms in relation to the control group. 27 The current study did not find a relationship between gender and nicotine craving.…”
Section: Discussionmentioning
confidence: 99%